Analisis Semiotika Lirik Lagu "Miracle" TXT dalam Album Minisode 3: Tomorrow - Putri Syaimah Martini; Kuwatono (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study analyzes the semiotic structure of the song lyrics “Miracle” by TXT through a qualitative approach using Saussurean and Barthesian frameworks. The analysis reveals that the lyrics construct symbolic meanings centered on hope, emotional struggle, and self-transformation, expressed through metaphors such as light, darkness, and movement. These linguistic signs illustrate an inner journey that reflects the psychological tension often experienced by adolescents, particularly when facing uncertainty and the need for self-affirmation. The denotative and connotative layers in the lyrics demonstrate how symbolic expressions generate emotional resonance, enabling listeners to relate to the narrative of searching for strength and clarity. The findings also show that the metaphor of light operates as the dominant signifier representing optimism and the belief in positive change. Overall, the song presents a cohesive symbolic narrative that portrays personal growth as a gradual and non-linear process. This study highlights how popular music serves not only as entertainment but also as a meaningful medium for expressing emotional realities and psychological development in contemporary youth.